A water-based thermofax foil ink-receptive layer and a method for preparing the same
Patent Information
- Application Number
- CN202611434703.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-16
- Publication Date
- 2026-10-23
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of ink-absorbing film materials, and in particular to an ink-absorbing layer for water-based hot stamping foil and its preparation method. Background Technology
[0002] The ink-absorbing layer, as a surface coating of inkjet printing media, plays a crucial role in rapidly absorbing ink, controlling diffusion and smudging, and fixing the color of the ink, thereby ensuring clear images, rich colors, and rapid drying. Existing ink-absorbing layer materials can be broadly classified into solvent-based ink-absorbing materials and water-based ink-absorbing materials. Solvent-based ink-absorbing film materials are made using oil-based polyurethane, acrylic, or vinyl chloride resin as film-forming agents, combined with a large amount of organic solvents (such as methyl ethyl ketone, toluene, and DMF). They have technical advantages such as good film-forming properties and acceptable adhesion to various substrates; however, they emit significant amounts of VOCs, failing to comply with environmental regulations, and solvent residues may affect the safety of the printed materials (such as food contact materials and infant products).
[0003] Water-based ink-absorbing materials, composed of water-based resins (such as polyurethane and acrylic acid) and added crosslinking agents (aziridine, carbodiimide, or isocyanate), possess excellent environmental performance and have gradually replaced solvent-based ink-absorbing film materials. However, water-based ink-absorbing materials are two-component systems, requiring preparation and immediate use, which makes them unsuitable for large-scale continuous production and storage, and they suffer from poor stability and short shelf life. Furthermore, inkjet-printing type water-based ink-absorbing layers developed in recent years, which do not contain pigments themselves and rely on ink printers to print ink patterns onto the surface for transfer, also suffer from unsuitability for large-scale continuous production and storage, and short shelf life. To address the problems of existing ink-absorbing film materials, the inventors provide a water-based hot stamping foil ink-absorbing layer and its preparation method. Summary of the Invention
[0004] To address the environmental issues and short service life of existing ink-absorbing film materials, this invention provides a water-based hot stamping foil ink-absorbing layer and its preparation method. The water-based hot stamping foil ink-absorbing layer is a single component that can crosslink and cure into a film at room temperature. It is stable during storage, has a long service life, and is suitable for large-scale continuous production and storage.
[0005] The water-based hot stamping foil ink-absorbing layer provided by this invention is achieved through the following technical solution: A water-based hot stamping foil ink-absorbing layer is made from the following raw materials in parts by weight: 50-70 parts water-based self-crosslinking polyurethane resin, 20-30 parts water-based polyester resin, 5-10 parts nano-fumed silica, 2-5 parts porous ink-absorbing particles, 0.1-1 parts wetting and leveling agent, 0.1-1 parts thickener, 0.1-1 parts defoamer, 0.5-2 parts emulsifier, 5-15 parts colorant, and 40-60 parts deionized water.
[0006] Preferably, the waterborne self-crosslinking polyurethane resin comprises diisocyanate, polyol composition, chain extender composition, end-capping agent A, catalyst, acetone, and deionized water. The end-capping agent A is prepared by a double-bonded monoisocyanate and mercaptosiloxane through a mercapto-olefin click chemical reaction. The double-bonded monoisocyanate is at least one selected from propylene 3-isocyanate, ethyl isocyanate methacrylate, 4-(maleimide)phenyl isocyanate, and 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0007] Preferably, the chain extender composition comprises a hydrophilic chain extender combined with at least one of ethylene glycol, 1,4-butanediol, and 1,6-hexanediol.
[0008] Preferably, the hydrophilic chain extender accounts for 2.9-3.2% of the dry weight of the waterborne self-crosslinking polyurethane resin.
[0009] Preferably, the diisocyanate is at least one of IPDI, HDI, and H12MDI.
[0010] Preferably, the hydrophilic chain extender is at least one of dimethylolpropionic acid, dimethylolbutyric acid, small molecule sulfonate diol BY-3306, and triethylamine dihydroxypropanesulfonic acid AJ-5570.
[0011] Preferably, the chain extender composition further includes 1,3-dihydroxyacetone, wherein the 1,3-dihydroxyacetone accounts for 0.5-1.0% of the dry weight of the waterborne self-crosslinking polyurethane resin.
[0012] Preferably, the waterborne self-crosslinking polyurethane resin further includes an accelerator, wherein the accelerator is at least one selected from succinic dihydrazide, adipate dihydrazide, and sebacic dihydrazide.
[0013] Preferably, the polyol composition is composed of polyether polyol and polycarbonate diol with a molecular weight of 800-3000; the polyether polyol is at least one of polytetrahydrofuran diol, tetrahydrofuran-propylene oxide copolymer diol, tetrahydrofuran-ethylene oxide copolymer diol combined with polyethylene oxide triol TP200 and polyethylene oxide tetraol PP150.
[0014] Preferably, the polycarbonate diol is a compound of polycarbonate diols PCDL 1011 and PCDL 1012.
[0015] More preferably, the polyol composition is composed of polyethylene oxide triol TP200, tetrahydrofuran-ethylene oxide copolydiol, polycarbonate diol PCDL 1011, and polycarbonate diol PCDL 1012 in a molar ratio of (8-10):(14-18):(8-10):(8-10).
[0016] The preparation method of the waterborne self-crosslinking polyurethane resin includes the following steps: S1, vacuum dehydration treatment of the polyol composition; Simultaneously, end-capping agent A is prepared by mixing a monoisocyanate containing a double bond with a mercaptosiloxane in an organic solvent, adding a photoinitiator, and reacting under UV light for 0.5-1.0 h to obtain end-capping agent A. S2, under nitrogen protection, the temperature of the polyol composition that has undergone vacuum dehydration is adjusted to 75-90℃, and diisocyanate and catalyst are added. The molar amount of NCO in the diisocyanate is 1.4-1.6 times the molar amount of -OH hydroxyl groups in the polyol composition. The reaction is maintained at 75-90℃ for 1-3 hours until the NCO content in the system reaches the theoretical value. S3, add chain extender composition, acetone, and remaining diisocyanate, and maintain the reaction at 75-90℃ for 1-3 hours until the NCO content in the system reaches 0; S4, adjust the temperature to 65-75℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 0.5-1.0h; S5, cool to 40-45℃, add triethylamine and / or dimethylethanolamine to neutralize and react for 3-5 minutes, adjust the pH to 7.0-7.5, then add deionized water for high-speed shear dispersion, distill off acetone, add accelerator, mix evenly, and you will get a waterborne self-crosslinking polyurethane resin with a solid content of 40-55%.
[0017] Preferably, the waterborne polyester resin is prepared by sulfonate polyester polyol and capping agent B; the sulfonate polyester polyol is at least one of BY-3303, BY-3305, and BY-3305B; the capping agent B is prepared by a double-bonded monoisocyanate and mercaptosiloxane through a mercapto-olefin click chemical reaction; the capping agent is at least one of propylene 3-isocyanate, isocyanoethyl methacrylate, 4-(maleimide)phenyl isocyanate, and 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0018] Preferably, the porous ink-absorbing particles are at least one of zeolite powder, halloysite powder, porous ceramic powder, diatomaceous earth, and porous MOFs powder with an average particle size of 100-500 nm.
[0019] Preferably, the wetting and leveling agent is a polyether-modified siloxane leveling agent.
[0020] Preferably, the thickener is a polyurethane associative thickener and / or an alkali-swellable thickener.
[0021] Preferably, the defoamer is a polyether-modified organosilicon.
[0022] Preferably, the emulsifier is at least one of the nonionic emulsifiers AEO-9, TX-10, and NP-10.
[0023] The present invention provides a method for preparing an ink-absorbing layer of water-based hot stamping foil, which is achieved through the following technical solution: A method for preparing an ink-absorbing layer of a water-based hot stamping foil includes the following steps: Step 1: Weigh out the nano-fumed silica, porous ink-absorbing particles, wetting and leveling agent, defoamer, emulsifier and deionized water according to the formula and disperse them evenly by high-speed shearing. Step 2: Add self-crosslinking polyurethane resin, water-based polyester resin, color powder, and thickener and mix evenly. Add pH adjuster to adjust the pH of the system to 7.0-7.5 to obtain water-based hot stamping foil ink-absorbing layer resin. When using it, coat the water-based hot stamping foil ink-absorbing layer resin from step two onto the release paper, and dry it at 60~80℃ to remove moisture, thus producing the water-based hot stamping foil ink-absorbing layer.
[0024] In summary, the present invention has the following advantages: 1. This invention is water-based and environmentally friendly, with no organic solvents or harmful monomer residues. It can be cross-linked and cured into a film at room temperature, exhibits excellent storage stability, has a long service life, and is suitable for large-scale continuous production and storage.
[0025] 2. The water-based hot stamping foil ink-absorbing layer in this invention can be hot stamped on various substrates such as textiles, transparent tablecloths (PVC / PU), leather, wood, metal, and glass, achieving "one foil for multiple uses" and significantly expanding the application scenarios of water-based hot stamping foil ink-absorbing layer products.
[0026] 3. The water-based hot stamping foil ink-absorbing layer in this invention achieves direct coloring by adding pigments internally, and the coating process is coloring, which simplifies the process chain, reduces equipment investment, and is especially suitable for mass production of single patterns.
[0027] 4. The water-based hot stamping foil ink-absorbing layer composition of the present invention is a single component with excellent storage stability. It can be stored at room temperature in a sealed container for ≥6 months and is ready to use immediately without any expiration date.
[0028] 5. The water-based hot stamping foil ink-absorbing layer composition of the present invention has good coating suitability. Through the synergistic effect of thickener, defoamer and emulsifier, a smooth, bubble-free and pinhole-free high-quality uniform ink-absorbing coating is obtained.
[0029] 6. The water-based hot stamping foil ink-absorbing layer in this invention has excellent hot stamping adhesion: 5B on fabric and PVC / PU using the cross-cut adhesion test, and ≥4B on leather, wood and other substrates, meeting the requirements for commercial use. Detailed Implementation
[0030] To further understand the inventiveness and technical advancements of this invention, the preferred embodiments of this invention will be discussed in detail below with reference to examples and comparative examples.
[0031] Example: An ink-absorbing layer for water-based hot stamping foil is made from the following raw materials in parts by weight: 50-70 parts water-based self-crosslinking polyurethane resin, 20-30 parts water-based polyester resin, 5-10 parts nano-fumed silica, 2-5 parts porous ink-absorbing particles, 0.1-1 parts wetting and leveling agent, 0.1-1 parts thickener, 0.1-1 parts defoamer, 0.5-2 parts emulsifier, 5-15 parts colorant, and 40-60 parts deionized water.
[0032] The porous ink-absorbing particles are at least one of the following: zeolite powder, halloysite powder, porous ceramic powder, diatomaceous earth, and porous MOF powder, with an average particle size of 100-500 nm.
[0033] The wetting and leveling agent is a polyether-modified siloxane leveling agent.
[0034] The thickener is a polyurethane associative thickener and / or an alkali-swellable thickener.
[0035] The defoamer is a polyether-modified silicone.
[0036] The emulsifier is at least one of the nonionic emulsifiers AEO-9, TX-10, and NP-10.
[0037] Waterborne self-crosslinking polyurethane resin includes diisocyanate, polyol composition, chain extender composition, end-capping agent A, catalyst, acetone, deionized water, and accelerator.
[0038] The diisocyanate is at least one of IPDI, HDI, and H12MDI.
[0039] End-capping agent A is prepared by a double-bonded monoisocyanate and a mercaptosiloxane via a mercapto-olefin click chemical reaction. The double-bonded monoisocyanate is at least one of propylene 3-isocyanate, isocyanoethyl methacrylate, 4-(maleimide)phenyl isocyanate, and 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0040] The chain extender composition comprises a hydrophilic chain extender combined with at least one of ethylene glycol, 1,4-butanediol, and 1,6-hexanediol.
[0041] The hydrophilic chain extender accounts for 2.9-3.2% of the dry weight of the water-based self-crosslinking polyurethane resin.
[0042] The hydrophilic chain extender is at least one of dimethylolpropionic acid, dimethylolbutyric acid, small molecule sulfonate diol BY-3306, and triethylamine dihydroxypropanesulfonic acid AJ-5570.
[0043] Preferably, the chain extender composition comprises a hydrophilic chain extender, 1,3-dihydroxyacetone combined with at least one of ethylene glycol, 1,4-butanediol, and 1,6-hexanediol. 1,3-dihydroxyacetone accounts for 0.5-1.0% of the dry weight of the waterborne self-crosslinking polyurethane resin. The accelerator is at least one of succinic dihydrazide, adipic dihydrazide, and sebacic dihydrazide. Under acidic room temperature conditions, the accelerator undergoes a nucleophilic addition-elimination condensation reaction with the ketone in 1,3-dihydroxyacetone, losing one molecule of water to form an acylhydrazone, which can improve the crosslinking density of the ink-absorbing film and optimize its heat resistance, abrasion resistance, and weather resistance.
[0044] The polyol composition consists of polyether polyols and polycarbonate diols with a molecular weight of 800-3000.
[0045] The polyether polyol is at least one of polytetrahydrofuran diol, tetrahydrofuran-propylene oxide copolydiol, tetrahydrofuran-ethylene oxide copolydiol, polyoxyethylene triol TP200, and polyoxyethylene tetraol PP150. The polycarbonate diol is a blend of polycarbonate diols PCDL 1011 and PCDL 1012.
[0046] Preferably, the polyol composition is composed of polyethylene oxide triol TP200, tetrahydrofuran-ethylene oxide copolymer diol, polycarbonate diol PCDL 1011, and polycarbonate diol PCDL 1012 in a molar ratio of (8-10):(14-18):(8-10):(8-10).
[0047] A method for preparing waterborne self-crosslinking polyurethane resin includes the following steps: S1, vacuum dehydration treatment of the polyol composition; Simultaneously, end-capping agent A is prepared by mixing a monoisocyanate containing a double bond with a mercaptosiloxane in an organic solvent, adding a photoinitiator, and reacting under UV light for 0.5-1.0 h to obtain end-capping agent A. S2, under nitrogen protection, the temperature of the polyol composition that has undergone vacuum dehydration is adjusted to 75-90℃, and diisocyanate and catalyst are added. The molar amount of NCO in the diisocyanate is 1.4-1.6 times the molar amount of -OH hydroxyl groups in the polyol composition. The reaction is maintained at 75-90℃ for 1-3 hours until the NCO content in the system reaches the theoretical value. S3, add chain extender composition and acetone, maintain reaction at 75-90℃ for 1-3h until the NCO content in the system reaches 0; S4, adjust the temperature to 65-75℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 0.5-1.0h; S5, cool to 40-45℃, add triethylamine and / or dimethylethanolamine to neutralize and react for 3-5 minutes, adjust the pH to 7.0-7.5, then add deionized water for high-speed shear dispersion, distill off acetone, add accelerator, mix evenly, and you will get a waterborne self-crosslinking polyurethane resin with a solid content of 40-55%.
[0048] Waterborne polyester resins are prepared by combining sulfonate polyester polyols with capping agent B.
[0049] The sulfonate polyester polyol is at least one of BY-3303, BY-3305, and BY-3305B.
[0050] End-capping agent B is prepared by a double-bonded monoisocyanate and a mercaptosiloxane via a mercapto-olefin click chemical reaction. The end-capping agent is at least one of propylene 3-isocyanate, isocyanoethyl methacrylate, 4-(maleimide)phenyl isocyanate, and 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
[0051] A method for preparing an ink-absorbing layer of a water-based hot stamping foil includes the following steps: Step 1: Weigh out the nano-fumed silica, porous ink-absorbing particles, wetting and leveling agent, defoamer, emulsifier and deionized water according to the formula and disperse them evenly by high-speed shearing. Step 2: Add self-crosslinking polyurethane resin, water-based polyester resin, color powder, and thickener and mix evenly. Add pH adjuster to adjust the pH of the system to 7.0-7.5 to obtain water-based hot stamping foil ink-absorbing layer resin. When using it, coat the water-based hot stamping foil ink-absorbing layer resin from step two onto the release paper, and dry it at 60~80℃ to remove moisture, thus producing the water-based hot stamping foil ink-absorbing layer.
[0052] Example 1: An ink-absorbing layer for water-based hot stamping foil is made from the following raw materials in parts by weight: 60 parts water-based self-crosslinking polyurethane resin, 25 parts water-based polyester resin, 6.5 parts nano-hydrophilic fumed silica (WACKER HDK® N20 fumed silica), 4 parts 600-mesh diatomaceous earth (Shijiazhuang Mengyu New Material Technology Co., Ltd.), 0.25 parts wetting and leveling agent BYK-333, 0.50 parts thickener (TEGO® ViscoPlus 3060), 0.25 parts defoamer (TEGO FOAMEX 825), 1.5 parts nonionic emulsifier AEO-9, 8 parts pigment - Bayer ultrafine iron oxide red 130M, and 55 parts deionized water.
[0053] The waterborne self-crosslinking polyurethane resin is composed of 10.1 parts polyethylene oxide triol TP200 (molecular weight 1010, Perstorp, USA), 30 parts polytetrahydrofuran glycol (molecular weight 2000, Hyosung Chemical (Jiaxing) Co., Ltd.), 10 parts polycarbonate diol PCDL 1011 (molecular weight 1000, Guangzhou Haoyi New Material Technology Co., Ltd.), and 20 parts polycarbonate diol PCDL. The mixture was prepared from 1012 (molecular weight 2000, Guangzhou Haoyi New Material Technology Co., Ltd.), 3.02 parts dimethylolpropionic acid (CAS: 4767-03-7, Beijing Bailingwei Technology Co., Ltd.), 2.92 parts 1,4-butanediol (CAS: 110-63-4, Shandong Chuangying Chemical Co., Ltd.), 21.12 parts isophorone diisocyanate IPDI (Wanhua Chemical Group Co., Ltd.), 1.20 parts γ-mercaptopropyltriethoxysilane (Hangzhou Jessica Chemical Co., Ltd.), 1 part 3-isopropenyl-α,α-dimethylbenzyl isocyanate (CAS: 2094-99-7, Hubei Jusheng Technology Co., Ltd.), 0.004 parts organic bismuth catalyst Coscat83 (Guangdong Yuanfeng Chemical Reagent Co., Ltd.), 25 parts acetone, and 100 parts deionized water.
[0054] A method for preparing waterborne self-crosslinking polyurethane resin includes the following steps: S1, respectively, performs vacuum dehydration treatment on polyethylene oxide triol TP200, polytetrahydrofuran diol PTMEG-2000, polycarbonate diol PCDL 1011, and polycarbonate diol PCDL 1012: vacuum is applied and dehydration treatment is carried out at 120℃ for 2 hours, and then set aside for later use. Simultaneously, end-capping agent A was prepared: Under nitrogen protection, 20.12 parts of 3-isopropenyl-α,α-dimethylbenzyl isocyanate and 23.84 parts of γ-mercaptopropyltriethoxysilane were fully dissolved in 80 parts of ethyl acetate. After mixing evenly, 0.5 parts of photoinitiator 2959 were added. The temperature was controlled at 0℃, and a 365 nm UV-LED light source was used. The reaction was carried out under UV-LED light irradiation for 0.5 h, with a cumulative light energy of 500 mJ / cm², to obtain end-capping agent A. S2, under nitrogen protection, weigh 10.1 parts of polyethylene oxide triol TP200, 30 parts of polytetrahydrofuran diol PTMEG-2000, 10 parts of polycarbonate diol PCDL 1011, and 20 parts of polycarbonate diol PCDL 1012. After mixing them evenly, adjust the temperature to 90℃, add 15 parts of isophorone diisocyanate IPDI and 0.004 parts of organic bismuth catalyst Coscat83, and maintain the reaction at 90℃ for 2.0 h until the NCO content in the system reaches the theoretical value; S3, add 3.02 parts of dimethylolpropionic acid, 2.92 parts of 1,4-butanediol, 25 parts of acetone, and the remaining 6.12 parts of diisocyanate, and maintain the reaction at 90°C for 3 hours until the NCO content in the system reaches 0; S4, adjust the temperature to 70℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 1.0 h; S5, cool to 40℃, add 0.20 parts of dimethylethanolamine to neutralize the reaction for 5 min, then add 100 parts of deionized water for high-speed shear dispersion for 10 min, remove acetone by distillation, add triethylamine to adjust the pH of the system to 7.2, mix evenly to obtain waterborne self-crosslinking polyurethane resin with a solid content of 49.7%.
[0055] A method for preparing waterborne polyester resin includes the following steps: S1, Preparation of capping agent B: Under nitrogen protection, 20.12 parts of 3-isopropenyl-α,α-dimethylbenzyl isocyanate and 23.84 parts of γ-mercaptopropyltriethoxysilane were fully dissolved in 80 parts of ethyl acetate. After mixing evenly, 0.5 parts of photoinitiator 2959 were added. The temperature was controlled at 0℃, and a 365 nm UV-LED light source was used. The reaction was carried out under UV-LED light irradiation for 0.5 h, with a cumulative light energy of 500 mJ / cm², to obtain capping agent B. S2, 100 parts of sulfonate polyester polyol BY-3305B (Beijing Baiyuan Chemical Co., Ltd., molecular weight 2000) were subjected to vacuum dehydration treatment: vacuum was applied and dehydration treatment was carried out at 120℃ for 2 hours, and then set aside for later use. S3, add end-capping agent B to sulfonate polyester polyol BY-3305B and mix evenly, add 0.004 parts of organic bismuth catalyst Coscat83, mix evenly, adjust the temperature to 80℃, maintain the reaction at 80℃ for 2.0h, until the NCO content in the system is 0; S4, add 144 parts of deionized water, disperse by high-speed shearing for 10 minutes, and remove acetone by distillation to obtain a waterborne polyester resin with a solid content of 49.9%.
[0056] A method for preparing an ink-absorbing layer of a water-based hot stamping foil includes the following steps: Step 1: Weigh out the following ingredients according to the specified ratio: nano-fumed silica HDK® N20, 600-mesh diatomaceous earth, wetting and leveling agent BYK-333, defoamer TEGO FOAMEX 825, nonionic emulsifier AEO-9, and deionized water, and disperse them evenly under high-speed shearing. Step 2: Add accurately measured self-crosslinking polyurethane resin, waterborne polyester resin, thickener - TEGO®ViscoPlus 3060, and ultrafine iron oxide red 130M and mix evenly. Add pH adjuster - triethylamine to adjust the pH of the system to 7.2 to obtain waterborne hot stamping foil ink absorption layer resin. In use, the water-based hot stamping foil ink-absorbing layer resin from step two is coated onto release paper and dried at 80°C to remove moisture, thus producing the water-based hot stamping foil ink-absorbing layer.
[0057] The difference between Example 2 and Example 1 is that the polyethylene oxide triol TP200 in the waterborne self-crosslinking polyurethane resin is replaced with polyethylene oxide triol PP150.
[0058] Specifically, the waterborne self-crosslinking polyurethane resin is prepared from 6 parts of polyethylene oxide triol PP150 (molecular weight 800, Perstorp, USA), 30 parts of polytetrahydrofuran diol PTMEG-2000, 10 parts of polycarbonate diol PCDL 1011, 20 parts of polycarbonate diol PCDL 1012, 3.02 parts of dimethylolpropionic acid, 2.92 parts of 1,4-butanediol, 21.12 parts of isophorone diisocyanate IPDI, 1.20 parts of γ-mercaptopropyltriethoxysilane, 1.0 part of 3-isopropenyl-α,α-dimethylbenzyl isocyanate, 0.004 parts of organic bismuth catalyst Coscat 83, 25 parts of acetone, and 95.2 parts of deionized water.
[0059] The difference between Example 3 and Example 1 is that the waterborne self-crosslinking polyurethane resin is prepared from 10.1 parts of polyethylene oxide triol TP200, 30 parts of polytetrahydrofuran diol PTMEG-2000, 10 parts of polycarbonate diol PCDL 1011, 20 parts of polycarbonate diol PCDL 1012, 1.12 parts of small molecule sulfonate diol BY-3306 (Beijing Baiyuan Chemical Co., Ltd., hydroxyl value 249.3 mgKOH / g), 2.68 parts of dimethylolpropionic acid, 2.92 parts of 1,4-butanediol, 21.12 parts of isophorone diisocyanate IPDI, 1.20 parts of γ-mercaptopropyltriethoxysilane, 1.0 part of 3-isopropenyl-α,α-dimethylbenzyl isocyanate, 0.004 parts of organic bismuth catalyst Coscat 83, 25 parts of acetone, and 96.0 parts of deionized water.
[0060] The difference in the preparation method of waterborne self-crosslinking polyurethane resin is as follows: S1 and S2 are the same; S3, add 1.12 parts of small molecule sulfonate diol BY-3306, 2.68 parts of dimethylolpropionic acid, 2.92 parts of 1,4-butanediol, 25 parts of acetone, and the remaining 6.12 parts of diisocyanate, and maintain the reaction at 90℃ for 3 hours until the NCO content in the system reaches 0; S4, adjust the temperature to 70℃, add the end-capping agent A prepared in S1, and the end-capping reaction is carried out for 1.0 hour; S5, cool down to 40℃, add 96.0 parts of deionized water and disperse by high-speed shearing for 10 minutes, remove acetone by distillation, add triethylamine to adjust the pH of the system to 7.2, and mix evenly to obtain waterborne self-crosslinking polyurethane resin with a solid content of 50.0%.
[0061] The difference between Example 4 and Example 1 is that the waterborne self-crosslinking polyurethane resin is composed of 10.1 parts polyethylene oxide triol TP200, 20 parts sulfonate polyester polyol BY-3305B, 30 parts polytetrahydrofuran diol PTMEG-2000, 5 parts polycarbonate diol PCDL 1011, and 10 parts polycarbonate diol PCDL. The product was prepared by using 1012 parts, 5.64 parts of small molecule sulfonate diol BY-3306, 3.16 parts of 1,4-butanediol, 0.68 parts of 1,3-dihydroxyacetone (CAS: 96-26-4, Beijing Bailingwei Technology Co., Ltd.), 0.66 parts of adipic acid dihydrazide (CAS: 1071-93-8, Beijing Bailingwei Technology Co., Ltd.), 21.12 parts of isophorone diisocyanate IPDI, 1.20 parts of γ-mercaptopropyltriethoxysilane, 1.0 part of 3-isopropenyl-α,α-dimethylbenzyl isocyanate, 0.004 parts of organobismuth catalyst Coscat 83, 25 parts of acetone, and 107.8 parts of deionized water.
[0062] The difference in the preparation methods of waterborne self-crosslinking polyurethane resin is as follows: S1 and S2 are the same; S3, add 0.66 parts of 1,3-dihydroxyacetone, 3.16 parts of 1,4-butanediol, 25 parts of acetone, and the remaining 6.12 parts of diisocyanate, and maintain the reaction at 90°C for 3 hours until the NCO content in the system reaches 0. S4, adjust the temperature to 70℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 1.0 h; S5, cool to 40℃, add 0.20 parts of dimethylethanolamine to neutralize the reaction for 5 min, then add 107.8 parts of deionized water for high-speed shear dispersion for 10 min, remove acetone by distillation, add triethylamine to adjust the pH of the system to 7.2, add 0.66 parts of adipic acid dihydrazide, mix at a low speed of 240 rpm for 8 min, and mix evenly to obtain a waterborne self-crosslinking polyurethane resin with a solid content of 50.0%.
[0063] The difference between Comparative Example 1 and Example 1 is that the two-component water-based hot stamping foil ink-absorbing layer is composed of component A and component B. Component A is made from the following raw materials in parts by weight: 60 parts water-based self-crosslinking polyurethane resin, 25 parts water-based polyester resin, 6.5 parts nano-hydrophilic fumed silica HDK® N20, 4 parts 600-mesh diatomaceous earth (Shijiazhuang Mengyu New Material Technology Co., Ltd.), 0.25 parts wetting and leveling agent BYK-333, 0.50 parts thickener (TEGO® ViscoPlus 3060), 0.25 parts defoamer (TEGOFOAMEX 825), 1.5 parts nonionic emulsifier AEO-9, 8 parts pigment - Bayer ultrafine iron oxide red 130M, and 55 parts deionized water. Component B is 1.3 parts isocyanate curing agent Wanhua HT100.
[0064] The difference between Comparative Example 2 and Example 1 is that the waterborne self-crosslinking polyurethane resin does not contain polyethylene oxide triol TP200. Specifically, the waterborne self-crosslinking polyurethane resin is prepared from 30 parts of polytetrahydrofuran diol PTMEG-2000, 20 parts of polycarbonate diol PCDL 1011, 35 parts of polycarbonate diol PCDL 1012, 3.02 parts of dimethylolpropionic acid, 2.92 parts of 1,4-butanediol, 21.12 parts of isophorone diisocyanate IPDI, 1.20 parts of γ-mercaptopropyltriethoxysilane, 1.0 part of 3-isopropenyl-α,α-dimethylbenzyl isocyanate, 0.004 parts of organobismuth catalyst Coscat 83, 25 parts of acetone, and 114.4 parts of deionized water.
[0065] The difference between Comparative Example 3 and Example 1 is that the water-based hot stamping foil ink-absorbing layer does not contain water-based polyester resin.
[0066] A water-based hot stamping foil ink-absorbing layer is made from the following raw materials in parts by weight: 85 parts water-based self-crosslinking polyurethane resin, 6.5 parts nano-hydrophilic fumed silica HDK® N20, 4 parts 600-mesh diatomaceous earth, 0.25 parts wetting and leveling agent BYK-333, 0.50 parts thickener - TEGO® ViscoPlus 3060, 0.25 parts defoamer - TEGO FOAMEX 825, 1.5 parts nonionic emulsifier AEO-9, 8 parts pigment - Bayer ultrafine iron oxide red 130M, and 55 parts deionized water.
[0067] Preparation method of water-based hot stamping foil ink-absorbing layer: Water-based hot stamping foil ink-absorbing resin is uniformly coated onto a patterned roller. Electroplated aluminum foil is prepared and passed through the patterned roller coated with the water-based hot stamping foil ink-absorbing resin. The foil is then dried in an oven at 105℃ for 120 seconds. After drying, the hot stamping film and PET release film are laminated and wound to obtain the finished hot stamping foil ink-absorbing product. Usage method of the finished hot stamping foil ink-absorbing product: The PET release film is peeled off. The ink-absorbing film layer of the finished hot stamping foil is then laminated with the substrate and passed through a hot stamping roller. The roller surface temperature is 125℃, and the speed is 0.5 m / s. After air drying, the ink-absorbing film layer is peeled off from the electroplated aluminum foil, thus forming a 35 μm thick ink-absorbing film layer on the PVC substrate.
[0068] The difference between Comparative Example 4 and Example 1 is that the waterborne self-crosslinking polyurethane resin was prepared from 10.1 parts of polyethylene oxide triol TP200, 20 parts of sulfonate polyester polyol BY-3305B, 30 parts of polytetrahydrofuran diol PTMEG-2000, 5 parts of polycarbonate diol PCDL 1011, 10 parts of polycarbonate diol PCDL 1012, 1.68 parts of dimethylolpropionic acid, 3.84 parts of 1,4-butanediol, 21.12 parts of isophorone diisocyanate IPDI, 1.20 parts of γ-mercaptopropyltriethoxysilane, 1.0 part of 3-isopropenyl-α,α-dimethylbenzyl isocyanate, 0.004 parts of organic bismuth catalyst Coscat 83, 25 parts of acetone, and 104.0 parts of deionized water.
[0069] A method for preparing waterborne self-crosslinking polyurethane resin includes the following steps: S1, respectively, performs vacuum dehydration treatment on polyethylene oxide triol TP200, polytetrahydrofuran diol PTMEG-2000, polycarbonate diol PCDL 1011, polycarbonate diol PCDL 1012, and sulfonate polyester polyol BY-3305B: vacuum is applied and dehydration treatment is carried out at 120℃ for 2 hours, and then set aside for later use; Simultaneously, end-capping agent A was prepared: Under nitrogen protection, 20.12 parts of 3-isopropenyl-α,α-dimethylbenzyl isocyanate and 23.84 parts of γ-mercaptopropyltriethoxysilane were fully dissolved in 80 parts of ethyl acetate. After mixing evenly, 0.5 parts of photoinitiator 2959 were added. The temperature was controlled at 0℃, and a 365 nm UV-LED light source was used. The reaction was carried out under UV-LED light irradiation for 0.5 h, with a cumulative light energy of 500 mJ / cm², to obtain end-capping agent A. S2, under nitrogen protection, weigh 10.1 parts of polyethylene oxide triol TP200, 20 parts of sulfonate polyester polyol BY-3305B, 30 parts of polytetrahydrofuran diol PTMEG-2000, 5 parts of polycarbonate diol PCDL 1011, and 10 parts of polycarbonate diol PCDL 1012. After mixing them evenly, adjust the temperature to 90℃, add 15 parts of isophorone diisocyanate IPDI and 0.004 parts of organic bismuth catalyst Coscat83, and maintain the reaction at 90℃ for 2.0 h until the NCO content in the system reaches the theoretical value. S3, add 1.68 parts of dimethylolpropionic acid, 3.84 parts of 1,4-butanediol, 25 parts of acetone, and the remaining 6.12 parts of diisocyanate, and maintain the reaction at 90°C for 3 hours until the NCO content in the system reaches 0; S4, adjust the temperature to 70℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 1.0 h; S5, cool to 40℃, add 0.11 parts of dimethylethanolamine to neutralize the reaction for 5 min, then add 104 parts of deionized water for high-speed shear dispersion for 10 min, remove acetone by distillation, add triethylamine to adjust the pH of the system to 7.2, mix evenly to obtain waterborne self-crosslinking polyurethane resin with a solid content of 49.9%.
[0070] The difference between Comparative Example 5 and Example 1 is that the content of the hydrophilic chain extender - dimethylolpropionic acid in the waterborne self-crosslinking polyurethane resin was adjusted to 4.0 wt% of the dry weight of the waterborne self-crosslinking polyurethane resin.
[0071] The waterborne self-crosslinking polyurethane resin is composed of 10.1 parts polyethylene oxide triol TP200 (molecular weight 1010, Perstorp, USA), 30 parts polytetrahydrofuran glycol (molecular weight 2000, Hyosung Chemical (Jiaxing) Co., Ltd.), 10 parts polycarbonate diol PCDL 1011 (molecular weight 1000, Guangzhou Haoyi New Material Technology Co., Ltd.), and 20 parts polycarbonate diol PCDL. The product was prepared from 1012 (molecular weight 2000, Guangzhou Haoyi New Material Technology Co., Ltd.), 4.02 parts dimethylolpropionic acid (CAS: 4767-03-7, Beijing Bailingwei Technology Co., Ltd.), 2.26 parts 1,4-butanediol (CAS: 110-63-4, Shandong Chuangying Chemical Co., Ltd.), 21.12 parts isophorone diisocyanate IPDI (Wanhua Chemical Group Co., Ltd.), 1.20 parts γ-mercaptopropyltriethoxysilane (Hangzhou Jessica Chemical Co., Ltd.), 1 part 3-isopropenyl-α,α-dimethylbenzyl isocyanate (CAS: 2094-99-7, Hubei Jusheng Technology Co., Ltd.), 0.004 parts organic bismuth catalyst Coscat83 (Guangdong Yuanfeng Chemical Reagent Co., Ltd.), 25 parts acetone, and 100 parts deionized water.
[0072] Performance testing: 1. 180° peel strength: The peel strength of the ink-absorbing film layer on the substrate is measured. The peel strength is tested according to GB / T 2792-2014.
[0073] 2. Test method for resistance to damp heat aging: The sample is placed in a constant temperature and humidity aging chamber. The damp heat aging conditions are: temperature 80℃, humidity 85%RH, damp heat aging time 168h. After damp heat aging is completed, the sample is naturally cooled to room temperature. The peel strength of the ink absorption film layer / substrate is determined according to GB / T 2792-2014.
[0074] 3. Adhesion test method: The adhesion performance of the ink-absorbing film layer shall be determined in accordance with ASTM D3359-09.
[0075] 4. Stability during room temperature sealed storage: If there is no stratification or sedimentation after centrifugation at 3000r / min for 15 min, it can be considered to have a room temperature storage period of more than 6 months.
[0076] Table 1: Test parameters of the ink-absorbing layer of water-based hot stamping foil in Examples 1-4 and Comparative Examples 1-5 Table 2: Processing performance parameters of the water-based hot stamping foil ink-absorbing layer in Examples 1-4 and Comparative Examples 1-5 Based on Examples 1-4 and Comparative Example 1, and referring to Tables 1-2, it can be seen that adding 1.3 parts of the isocyanate curing agent Wanhua HT100 to Comparative Example 1 resulted in a water-based hot stamping foil ink-absorbing layer with higher peel strength and better adhesion. However, after being freshly mixed at room temperature, the coating gradually thickens and forms a gel. Furthermore, Wanhua HT100 readily reacts with water, forming pinholes inside or on the surface of the coating. This can corrode the aluminum layer surface, leading to decreased gloss, dark spots, or discoloration.
[0077] Based on Examples 1-4 and Comparative Example 2, and referring to Tables 1-2, it can be seen that the waterborne self-crosslinking polyurethane resin in Comparative Example 2 lacks only polyethylene oxide triol TP200. The peel strength of the prepared waterborne hot stamping foil ink-absorbing layer is abnormally high, and the number-average dispersion is large, which is not conducive to stable hot stamping. Furthermore, the adhesion of this waterborne hot stamping foil ink-absorbing layer only reaches 2B, which is insufficient to meet the requirements for printing adhesion. After aging, the hot stamping layer shows obvious cracks and peeling, indicating insufficient system flexibility and interfacial bonding. Therefore, polyethylene oxide triol TP200 is a necessary raw material for synthesizing waterborne self-crosslinking polyurethane resin. Using the waterborne self-crosslinking polyurethane resin provided in this invention can guarantee the quality of the waterborne hot stamping foil ink-absorbing layer.
[0078] Based on Examples 1-4 and Comparative Example 3, and referring to Tables 1-2, it can be seen that Comparative Example 3 contains no water-based polyester resin at all, and the peel strength of the water-based hot stamping foil ink-absorbing layer is far below the industry standard, making effective hot stamping transfer impossible. Furthermore, the prepared water-based hot stamping foil ink-absorbing layer has no chemical bond with the aluminum layer interface; adhesion relies solely on weak physical adsorption, resulting in extremely poor fastness. After testing with 3M tape, the hot stamping layer peeled off over 65% of its area, completely failing to meet the requirements for use with electroplated aluminum. After aging, the coating becomes powdery and brittle, losing its protective and decorative functions.
[0079] Based on Examples 1-4 and Comparative Examples 4-5, and in conjunction with Table 1-2, it can be seen that a high content of sulfonic acid groups in BY-3305B or a high content of carboxyl groups in DMPA will lead to poor resin leveling in the ink-absorbing layer of the water-based hot stamping foil. In Comparative Example 4, dark spots and decreased gloss in the hot stamping area indicate that the hydrolysis products of sulfonic acid groups have corroded the aluminum layer. In Comparative Example 5, pinholes appear. Therefore, the content of the hydrophilic chain extender should be controlled at 2.8-3.2 wt%.
[0080] In summary, the water-based hot stamping foil ink-absorbing layer resin provided in this invention is a fully water-based system with significant environmental advantages: it contains no organic solvents or harmful monomer residues; and it can cross-link and cure at room temperature to form an ink-absorbing film layer, exhibiting excellent storage stability and a long service life, making it suitable for large-scale continuous production and storage.
Claims
1. A water-based hot stamping foil ink-absorbing layer, characterized in that: The water-based hot stamping foil ink-absorbing layer is made from the following raw materials in parts by weight: 50-70 parts water-based self-crosslinking polyurethane resin, 20-30 parts water-based polyester resin, 5-10 parts nano-fumed silica, 2-5 parts porous ink-absorbing particles, 0.1-1 parts wetting and leveling agent, 0.1-1 parts thickener, 0.1-1 parts defoamer, 0.5-2 parts emulsifier, 5-15 parts pigment, and 40-60 parts deionized water; the water-based self-crosslinking polyurethane resin includes diisocyanate, polyol composition, chain extender composition, end-capping agent A, catalyst, acetone, and deionized water, wherein the end-capping agent A is prepared by a double-bonded monoisocyanate and mercaptosiloxane through a mercapto-olefin click chemical reaction; the double-bonded monoisocyanate is propylene 3-isocyanate, isocyanoethyl methacrylate, or 4-(maleimide). The chain extender composition comprises at least one of phenyl isocyanate and 3-isopropenyl-α,α-dimethylbenzyl isocyanate; the chain extender composition comprises a hydrophilic chain extender combined with at least one of ethylene glycol, 1,4-butanediol, and 1,6-hexanediol; the hydrophilic chain extender accounts for 2.9-3.2% of the dry weight of the waterborne self-crosslinking polyurethane resin; the diisocyanate is at least one of IPDI, HDI, and H12MDI; the hydrophilic chain extender is at least one of dimethylolpropionic acid, dimethylolbutyric acid, small molecule sulfonate diol BY-3306, and triethylamine dihydroxypropanesulfonic acid AJ-5570.
2. The water-based hot stamping foil ink-absorbing layer according to claim 1, characterized in that: The chain extender composition further includes 1,3-dihydroxyacetone, wherein the 1,3-dihydroxyacetone accounts for 0.5-1.0% of the dry weight of the waterborne self-crosslinking polyurethane resin; the waterborne self-crosslinking polyurethane resin further includes an accelerator, wherein the accelerator is at least one selected from succinic acid dihydrazide, adipic acid dihydrazide, and sebacic acid dihydrazide.
3. The water-based hot stamping foil ink-absorbing layer according to claim 1, characterized in that: The polyol composition is composed of polyether polyols and polycarbonate diols with a molecular weight of 800-3000; the polyether polyol is at least one of polytetrahydrofuran diol, tetrahydrofuran-propylene oxide copolyol, tetrahydrofuran-ethylene oxide copolyol combined with polyethylene oxide triol TP200 and polyethylene oxide tetraol PP150; the polycarbonate diol is a compound composition of polycarbonate diols PCDL 1011 and PCDL1012.
4. The water-based hot stamping foil ink-absorbing layer according to claim 3, characterized in that: The polyol composition is composed of polyethylene oxide triol TP200, tetrahydrofuran-ethylene oxide copolydiol, polycarbonate diol PCDL 1011, and polycarbonate diol PCDL 1012 in a molar ratio of (8-10):(14-18):(8-10):(8-10).
5. The water-based hot stamping foil ink-absorbing layer according to claim 2, characterized in that: The preparation method of the waterborne self-crosslinking polyurethane resin includes the following steps: S1, vacuum dehydration treatment of the polyol composition; Simultaneously, end-capping agent A is prepared by mixing a monoisocyanate containing a double bond with a mercaptosiloxane in an organic solvent, adding a photoinitiator, and reacting under UV light for 0.5-1.0 h to obtain end-capping agent A. S2, under nitrogen protection, the temperature of the polyol composition that has undergone vacuum dehydration is adjusted to 75-90℃, and diisocyanate and catalyst are added. The molar amount of NCO in the diisocyanate is 1.4-1.6 times the molar amount of -OH hydroxyl groups in the polyol composition. The reaction is maintained at 75-90℃ for 1-3 hours until the NCO content in the system reaches the theoretical value. S3, add chain extender composition, acetone, and remaining diisocyanate, and maintain the reaction at 75-90℃ for 1-3 hours until the NCO content in the system reaches 0; S4, adjust the temperature to 65-75℃, add the end-capping agent A prepared in S1, and perform the end-capping reaction for 0.5-1.0h; S5, cool to 40-45℃, add triethylamine and / or dimethylethanolamine to neutralize and react for 3-5 minutes, adjust the pH to 7.0-7.5, then add deionized water for high-speed shear dispersion, distill off acetone, add accelerator, mix evenly, and you will get a waterborne self-crosslinking polyurethane resin with a solid content of 40-55%.
6. The water-based hot stamping foil ink-absorbing layer according to claim 2, characterized in that: The waterborne polyester resin is prepared by sulfonate polyester polyol and capping agent B; the sulfonate polyester polyol is at least one of BY-3303, BY-3305, and BY-3305B; the capping agent B is prepared by a double-bonded monoisocyanate and mercaptosiloxane through a mercapto-olefin click chemical reaction; the capping agent is at least one of propylene 3-isocyanate, isocyanoethyl methacrylate, 4-(maleimide)phenyl isocyanate, and 3-isopropenyl-α,α-dimethylbenzyl isocyanate.
7. The water-based hot stamping foil ink-absorbing layer according to claim 1, characterized in that: The porous ink-absorbing particles are at least one of zeolite powder, halloysite powder, porous ceramic powder, diatomaceous earth, and porous MOFs powder with an average particle size of 100-500 nm; the wetting and leveling agent is a polyether-modified siloxane leveling agent; the thickener is a polyurethane associative thickener and / or an alkali-swellable thickener; the defoamer is a polyether-modified organosilicon; and the emulsifier is at least one of nonionic emulsifiers AEO-9, TX-10, and NP-10.
8. A method for preparing an ink-absorbing layer of water-based hot stamping foil according to any one of claims 1-7, characterized in that: Includes the following steps: Step 1: Weigh out the nano-fumed silica, porous ink-absorbing particles, wetting and leveling agent, defoamer, emulsifier and deionized water according to the formula and disperse them evenly by high-speed shearing. Step 2: Add self-crosslinking polyurethane resin, water-based polyester resin, color powder, and thickener and mix evenly. Add pH adjuster to adjust the pH of the system to 7.0-7.5 to obtain water-based hot stamping foil ink-absorbing layer resin. When using it, coat the water-based hot stamping foil ink-absorbing layer resin from step two onto the release paper, and dry it at 60~80℃ to remove moisture, thus producing the water-based hot stamping foil ink-absorbing layer.